Manfaat dari Produk Biskuit dan Roti Fortifikasi Bubuk Nanas: Review - Rachma Anggaratih; Rahmawati Rahmawati (Program Studi Gizi UNSIKA, 2022)
Overweight and obesity are defined as abnormal or excessive fat accumulation that can interfere with health. Deaths due to obesity are higher than deaths from underweight. One of the causes of the increase in obesity is an unhealthy diet. The majority of people who live in cities consume fast food which can increase the value of body mass index. The addition pineapple powder as fortificant can increase food fiber content. Pineapple powder was able to increase the fiber content in the modified product. Products that have been added with pineapple powder can prevent or reduce the risk of diabetes, coronary heart disease, and hypertension.